(3GdVQGFH heMGSHJgG Hjf GdfXQjI hGdJWHjbs - (3eMeO(B, (3CHh fUGQs; (3eMahX GdeTGYdI(B;(3aQGS YWG Gddg GdTghGf(B, s ((3YeGf(B:s ((3O f(B),s, 2003)
(3GdJYQja HGdVQjHI hNUGFUgG, eONd dbGfhf VQjHI GdONd aj GdCQOf, eUGOQ GdONd GdNGVYI ddVQjHI, fabGJ GdYed GdebHhdI hZjQ GdebHhdI VQjHjG, GdCMcGe GdYGeI hGdfhGMj GdCLQGFjI dbGfhf VQjHI GdONd, VQjHI GdONd Ydi GdQhGJH hGdCLhQ, eONd dELQGAGJ GdJbOjQ Ydi eNJda Gdecdajf, bWGY TQcGJ GdCTNGU, bWGY GdTQcGJ GdJLGQjI hGdUfGYjI, bWGY TQcGJ GdebGhdGJ, bWGY GdUQGaI hGdhSGWI, bWGY TQcGJ GdJCejf, GdbWGY GdeUQaj hGdeGdj hGdTQcGJ GdJj JbHd GdhOGFYs
Keywords: (3GdVQGFHs; (3GdeMGSHIs; (3eMGSHI(B- (3GdVQGFHs